Novel In Situ Gelling Hydrogels Loaded with Recombinant Collagen Peptide Microspheres as a Slow‐Release System Induce Ectopic Bone Formation. Issue 21 (19th September 2018) - Fahmy‐Garcia, Shorouk; Mumcuoglu, Didem; de Miguel, Laura; Dieleman, Veerle; Witte‐Bouma, Janneke; van der Eerden, Bram C. J.; van Driel, Marjolein; Eglin, David; Verhaar, Jan A. N.; Kluijtmans, Sebastiaan G. J. M.; van Osch, Gerjo J. V. M.; Farrell, Eric
Abstract: New solutions for large bone defect repair are needed. Here, in situ gelling slow release systems for bone induction are assessed. Collagen‐I based Recombinant Peptide (RCP) microspheres (MSs) are produced and used as a carrier for bone morphogenetic protein 2 (BMP‐2). The RCP‐MSs are dispersed in three hydrogels: high mannuronate (SLM) alginate, high guluronate (SLG) alginate, and thermoresponsive hyaluronan derivative (HApN). HApN+RCP‐MS forms a gel structure at 32 ºC or above, while SLM+RCP‐MS and SLG+RCP‐MS respond to shear stress displaying thixotropic behavior. Alginate formulations show sustained release of BMP‐2, while there is minimal release from HApN. These formulations are injected subcutaneously in rats. SLM+RCP‐MS and SLG+RCP‐MS loaded with BMP‐2 induce ectopic bone formation as revealed by X‐ray tomography and histology, whereas HApN+RCP‐MS do not. Vascularization occurs within all the formulations studied and is significantly higher in SLG+MS and HApN+RCP‐MS than in SLM+RCP‐MS. Inflammation (based on macrophage subset staining) decreases over time in both alginate groups, but increases in the HApN+RCP‐MS condition. It is shown that a balance between inflammatory cell infiltration, BMP‐2 release, and vascularization, achieved in the SLG+RCP‐MS alginate condition, is optimal for the induction of de novo bone formation. Abstract : In situ gelling release systems for bone induction are investigated in an ectopic rat model. Collagen recombinant peptide microspheres (RCP‐MS) are used as a carrier for low‐dose bone morphogenetic protein‐2 (BMP‐2) and embedded in either alginate or thermoresponsive hyaluronan derivative hydrogels. Alginate+RCP‐MS shows optimal BMP‐2 release kinetics, resulting in the greatest amount of bone formation at 10 weeks' time.